Intracranial evaluation of the epileptogenic zone in regional infrasylvian polymicrogyria. (18th September 2012) - Ramantani, Georgia; Koessler, Laurent; Colnat‐Coulbois, Sophie; Vignal, Jean‐Pierre; Isnard, Jean; Catenoix, Hélène; Jonas, Jacques; Zentner, Josef; Schulze‐Bonhage, Andreas; Maillard, Louis Georges
Summary Purpose: To define the relationship between the epileptogenic zone and the polymicrogyric area using intracranial electroencephalography (EEG) recordings in patients with structural epilepsy associated with regional infrasylvian polymicrogyria (PMG). Methods: We retrospectively reviewed the medical charts, scalp, and intracranial video‐EEG recordings, neuroimaging findings, and neuropsychological evaluations of four patients with refractory temporal lobe epilepsy related to PMG who consequently underwent resective surgery. Key Findings: High‐resolution magnetic resonance imaging (MRI) revealed temporal lobe PMG in all cases, accompanied by hippocampal malrotation and closed lip schizencephaly in 3/4 cases, respectively. In intracranial recordings, interictal spike activity was localized within the PMG in only 2/4 and within the amygdala, hippocampus, and entorhinal cortex in all cases. In the first patient, two epileptogenic networks coexisted: the prevailing network initially involved the mesial temporal structures with spread to the anterior PMG; the secondary network successively involved the anterior part of the PMG and later the mesial temporal structures. In the second patient, the epileptogenic network was limited to the mesial temporal structures, fully sparing the PMG. In the third patient, the epileptogenic network first involved the mesial temporal structures and later the PMG. Conversely, in the last case, part of the PMG harbored an epileptogenic network that propagated to the mesial temporal structures. Consistent with these findings a favorable outcome (Engel class I in three of four patients; Engel class II in one of four) at last follow‐up was obtained by a resection involving parts of the PMG cortex in three of four and anteromesial temporal lobe structures in another three of four cases. Significance: Infrasylvian PMG displays a heterogeneous epileptogenicity and is occasionally and partially involved in the epileptogenic zone that commonly includes the mesial temporal structures. Our results highlight the intricate interrelations between the MRI‐detectable lesion and the epileptogenic zone as delineated by intracranial recordings. Seizure freedom can be accomplished as a result of a meticulous intracranial study guiding a tailored resection that may spare part of the PMG.